Using graphic comparison to explore the dynamic relationship between social conflicts and Fujian Defense-Dwellings in China. Issue 6 (2nd November 2022) - Qin, Qiaohua; Xiao, Dawei; Ma, Junwei; Tao, Jin
ABSTRACT: This article focuses on the large number of existing defense-dwellings built in the Ming and Qing dynasties with distinct regional characteristics in Fujian, and explores the relationship between major conflicts and defense-dwellings. A four-year field survey involving 459 historic villages was conducted. ArcGis was used to superimpose the high-resolution satellite map of Fujian with the borders of towns to classify defense-dwellings and establish the attribute database. By comparing the spatial types and their provincial distribution characteristics, and analyzing them with the conflicts in Fujian history, this paper presents a unique relationship between the unity and diversity of space forms and how they changed or were maintained. The results show: 1. Major military conflicts had a profound and lasting impact on the spatial pattern, residential form, and daily life of historic villages in Fujian; 2. The time and space difference of regional conflicts makes defense-dwellings present a distribution state of different types of central gathering and edge transition; 3. Persistent conflict for limited resources between clan groups made defense-dwellings remain vital, finally forming a typical "architectural atlas". The results of this study are helpful in understanding the systematic view of morphological changes of historic villages in a highly conflicting social environment.